2022
DOI: 10.3390/met12111988
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Magnetic Field Regulated Mechanical Property of Solid Metal Materials

Abstract: During the material preparation process, the magnetic field can act with high intensity energy on the material without contact and affect its microstructure and properties. This non-contact processing method, which can change the microstructure and properties of material without affecting the shape and size of products, has become an important technical means to develop new materials and optimize the properties of materials. It has been widely used in scientific research and industrial production. In recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…According to the above theory, it can be inferred that the dislocation in the aluminium bronze alloy becomes more easily depinned and moved under the influence of the original stress field, due to the change in the electronic energy state at the pinned place during the pulsed magnetic field treatment. On the one hand, the dislocation movement reduced the stress concentration caused by the dislocation pile-up, relaxed the original stress, and reduced the residual stress of the alloy, as verified by the significant reduction in residual stress in the magnetic field treatment of aluminium alloy [ 7 ], nickel–aluminium bronze [ 9 ], EN8 special steel [ 10 ], titanium alloy [ 26 ], and magnesium alloy [ 27 ]. On the other hand, the dislocation movement somewhat altered the grain boundary angle, resulting in an apparent reduction in LAGBs and the disappearance of twin boundaries, which lowered the system energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the above theory, it can be inferred that the dislocation in the aluminium bronze alloy becomes more easily depinned and moved under the influence of the original stress field, due to the change in the electronic energy state at the pinned place during the pulsed magnetic field treatment. On the one hand, the dislocation movement reduced the stress concentration caused by the dislocation pile-up, relaxed the original stress, and reduced the residual stress of the alloy, as verified by the significant reduction in residual stress in the magnetic field treatment of aluminium alloy [ 7 ], nickel–aluminium bronze [ 9 ], EN8 special steel [ 10 ], titanium alloy [ 26 ], and magnesium alloy [ 27 ]. On the other hand, the dislocation movement somewhat altered the grain boundary angle, resulting in an apparent reduction in LAGBs and the disappearance of twin boundaries, which lowered the system energy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have tried to directly put metal materials in a strong magnetic field to study the impact of magnetic field treatment on material structure and properties. It was found that magnetic field treatment had apparent effects on improving the strength, plasticity, hardness, wear resistance, fatigue resistance, and many other properties of metal materials [ 7 ]. Reference [ 8 ] observed that after constant magnetic field treatment of 7055 aluminium alloy, the cellular dislocation transformed to network dislocation to form a subcrystal, which positively affected grain refinement, and η(MgZn 2 ) transformed to the η′ phase.…”
Section: Introductionmentioning
confidence: 99%
“…This can achieve better impedance matching with air, thereby reducing coating thickness and increasing electromagnetic-absorption bandwidth. They are ideal choices for developing high-performance electromagnetic-absorption materials [26]. As a typical magnetic metal powder, carbonyl iron powder (CIP) has been widely used as an absorbent, due to the high magnetic permeability, high saturation magnetization, high Curie temperature, excellent absorption performance, and wide electromagnetic-absorption frequency band [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%